Comparative exergoeconomic analysis of atmosphere and pressurized CLC power plants coupled with supercritical CO2 cycle. (15th February 2023) - Wang, Yuan; Zhu, Lin; He, Yangdong; Yu, Jianting; Zhang, Chaoli; Wang, Zi
Abstract: Recently, the incorporation of chemical looping combustion (CLC) and sCO2 Brayton cycle has been regarded as a promising technology for clean and efficient power generation. The intrinsic characteristics of the CLC reactors (interconnected circulating fluidized bed or fixed bed) allow them to operate at different pressures, leading to different technological directions. Therefore, a pair of "CLC coupled sCO2 cycle" systems was proposed, namely the atmosphere CLC (A-CLC-sCO2 ) and pressurized CLC (P-CLC-sCO2 ). The purpose of this paper is to determine which configuration holds more benefits from a combined exergetic and economic perspective. The operational boundary conditions for thermodynamic advantage of P-CLC-sCO2 over the optimized A-CLC-sCO2 was firstly investigated. Under respective optimal conditions, the exergy efficiency of P-CLC-sCO2 (51.09%) was found to be 1.16% higher than that of A-CLC-sCO2 (49.91%). Besides, the P-CLC-sCO2 exhibited a lower levelized cost of electricity (79.59 $/MWh) than A-CLC-sCO2 (81.31 $/MWh) when using a nickel-based oxygen carrier (OC), but the A-CLC-sCO2 could further reduce LCOE to 78.93 $/MWh by adopting ilmenite-based OC. In addition, the exergy and exergoeconomic analysis of the main components was carried out to find the system improvement strategies. Highlights: The sCO2 cycle was thermally coupled with CLC unit for power generation. The boundary conditions for P -CLC-sCO2 to be superior to A-CLC-sCO2 were studied. Cost reduction potential for A-CLC-sCO2 system was revealed. Comparative exergoeconomic analysis was exerted to find improvement strategies.